Knowledge, Responsibilities, and Peer Advice From Care Partners of Patients With Parkinson Disease Psychosis - Mantri, Sneha; Edison, Briana; Alzyoud, Lamees; Albert, Steven M.; Daeschler, Margaret; Kopil, Catherine; Marras, Connie; Chahine, Lana M. (Frontiers in Neurology, 2021)
Introduction: Care partners (CPs) of individuals with Parkinson disease psychosis (PDP) experience increased strain and rely on informal support networks. The objective of this study was to characterize CP responsibilities, sources of support, and peer advice. Methods: This was a mixed-methods cross-sectional study. The sample was recruited from the online Fox Insight study cohort. CPs who indicated their care recipient suffered hallucinations and/or delusions were administered a questionnaire regarding their caregiving experience to person with PDP. A free-text question asked CPs to give advice to a hypothetical peer CP. Responses to multiple-choice questions were tabulated; responses to the free-text question were grouped into advice categories. Results: 145 CP of individuals with PDP were included in this analysis, mean age (standard deviation, SD) 66.4 (9.4) years; 110 (75.9%) were women. Most (115, 79.3%) provided caregiving on a daily basis, with a range of responsibilities. Only 16 (11%) learned about PDP from a physician; communication challenges included perceived embarrassment or having to prioritize other issues in a limited appointment time. The most common peer advice was to alert the care recipient's neurologist (n = 38, 30.4%); only 8 (6.4%) suggested medication changes. Conclusion: CPs face challenges with clinician communication and learn about psychosis from a variety of informal sources. Few CPs advocate for medications to control PDP, instead preferring non-pharmacological management strategies. Peer advice favored alerting the care recipient's physician, suggesting that CPs do desire more information from the medical team.